Hypothyroidism with too Many Associations Case Report (Journal of Armed Forces Medical College, Bangladesh, 2022)
Hypothyroidism is one of the common endocrine disorders. Amongst other causes, autoimmune hypothyroidism is clinically more important. It has got many adverse effects on metabolism, cardiovascular, musculoskeletal, fetomaternal and mental health. It's associated with obesity, dyslipidemia, IHD, inflammatory myopathy, depression etc. It is responsible for menorrhagia, subfertility, recurrent abortion, prematurity, fetomaternal morbidity and mortality. It may be associated with other organ specific or multisystem autoimmune diseases like SLE, vitiligo, alopecia, type-I DM, pernicious anemia and others. We have diagnosed a case of autoimmune hypothyroidism who had all the classic features of hypothyroidism. He had low FT4 and very high TSH. Autoimmunity was confirmed by high titer of anti TG and anti TPO antibody. In addition he had dimorphic anaemia, alopecia, diastolic hypertension, dyslipidemia, IHD, Vit D deficiency, myopathy, peripheral neuropathy, depression and dementia. His condition has been improved with Thyroxin replacement, lipid lowring drugs, anti anginal drugs, iron, calcium, folic acid, Vit-D supplementations, exercise, physiotherapy and other symptomatic and supportive measures. He was advised for consultation with dermatologist and periodic follow up.JAFMC Bangladesh. Vol 17, No 1 (June) 2021: 42-45